Hubungan Efikasi Diri Dan Ansietas Terhadap Mahasiswa Skripsi - Anita Pratamah; Aprida Manurung; Alda Elvariani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
To identify whether there is a relationship between self-efficacy and anxiety in nursing students at the Faculty of Health Sciences, Musi Charitas Catholic University who is currently writing a thesis. This article uses a quantitative descriptive method with a sample of 35 respondents in this study. The majority of respondents are female as many as 32 people (91.4%). A total of 27 (77.1%) respondents had a high level of self-efficacy, but as many as 16 (45.7%) respondents also experienced anxiety in the moderate range. The results of Kendall's Tau-B test found that there was no relationship between self-efficacy (p = 0.933 > 0.05) and anxiety (p = 0.933 > 0.05). Students must improve their self-efficacy so that they do not easily feel anxiety, and can be responsible for carrying out tasks so that they can write a thesis better and can concentrate fully.